Strategies to reduce the cancer burden and improve access to effective and affordable cancer interventions in Europe - Anton Berns; Ulrik Ringborg; Julio Celis; Bengt Jönsson; Michael Baumann (Molecular Oncology)
The development of new anticancer treatments, their clinical evaluation and introduction into the healthcare system need improvement. New drugs and cell therapies often come with significant costs for society while only marginally improving patients' survival and health‐related quality‐of‐life. Therefore, bold, innovative clinical trials with critical assessment of the efficacy and cost‐effectiveness of new preventive measures and medical treatments are needed to ensure that patients and society benefit. Drug development programmes controlled by pharma should be complemented with initiatives such as stop studies, dose reduction, combination and repurposing trials. These should be validated in academia‐initiated trials supported by societal funds. Special attention should be devoted to paediatric and rare adult cancers. Comprehensive Cancer Centres (CCCs) covering the entire cancer research continuum, present throughout the EU, are critical for this. More of such centres must be established concomitantly with a robust accreditation methodology to ensure that they meet appropriate quality standards. It is crucial that funding for these initiatives, now temporarily and partially provided by the EU Cancer Mission and Europe's Beating Cancer Plan, is secured for a much longer period.